(untitled) (Colombia Medica, 1987)
Several anopheline species of the subgenus Nyssorrhynchus, among them Anopheles nuñestovari, were recently shown to be present in Bajo Calima (Colombian Pacific Coast), where malaria is endemic. A short entomological survey using human bait was carried out in this area to determine the role of A. nuñeztovari in malaria transmission. It was established that A. nuñeztovari is not only susceptible to infection with Plasmodium sp. but also is markedly anthropophilic, has adequate longevity, has domestic biting habits, and, although its population density is not high, there is malaria transmission throughout the year. It is discussed that lumbering, road building, and the establishment of progressively larger human groups have greatly altered the premontane pluvial forest, the ecological niche of A. (Kerteszia) neivai. Erosion has blocked the drainage capacity of the soil, inducing the formation of terrestrial breeding places, which become permanent due to the constant rainfall and are colonized by species of subgenus Nyssorrhynchus like. A. nuñeztovari, whose vectorial capacity was demonstrated.